2004
DOI: 10.1088/0953-2048/17/8/026
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of spontaneous magnetization in large-scale two-dimensional hexagonal superconducting  -ring arrays

Abstract: We present an analytical investigation on the spontaneous magnetization of infinitely large two-dimensional identical hexagonal superconducting π-ring arrays based on an ansatz that each of the π-rings carries a magnetic flux with the same frustration index. The free energies per ring, Un, in various states characterized by the number of zero-current (‘quiet’) junctions n in the ring are calculated. A ladder relation of the energies has been demonstrated as , which basically shows that the fewer the quiet jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They studied the ordering of half flux quanta in these π-loop arrays, and moreover the possibility of manipulating the polarizations of individual half flux quanta in hexagonal π-loop arrays. Their experimental results as well as the analysis given by other authors [6,14] show that there is a general tendency to antiferromagnetic ordering of spontaneous magnetization fluxes of π-loop arrays in the absence of external field. Based on their results, the ordering of the half flux quanta in largescale one-dimensional π-loop arrays in a uniform external magnetic field is analysed via the free energy approach in this paper.…”
Section: Introductionmentioning
confidence: 61%
“…They studied the ordering of half flux quanta in these π-loop arrays, and moreover the possibility of manipulating the polarizations of individual half flux quanta in hexagonal π-loop arrays. Their experimental results as well as the analysis given by other authors [6,14] show that there is a general tendency to antiferromagnetic ordering of spontaneous magnetization fluxes of π-loop arrays in the absence of external field. Based on their results, the ordering of the half flux quanta in largescale one-dimensional π-loop arrays in a uniform external magnetic field is analysed via the free energy approach in this paper.…”
Section: Introductionmentioning
confidence: 61%
“…[11−14] Recently, Hilgenkamp et al have reported the realization of large-scale coupled π-loop arrays based on YBa 2 Cu 3 O 7 -Au-Nb Josephson contacts. [15,16] Their experimental results as well as the analysis given by other authors [8,17,18] showed a robust antiferromagnetic ordering of spontaneous magnetization in both square and triangular π-loop arrays and predominant anti-ferromagnetic nearest-neighbour coupling of half-flux quanta in hexagonal π-loop arrays in the absence of an external field. Very recently, the free energy densities in possible flux states of twodimensional square π-loop arrays in an external magnetic field were given analytically and compared numerically by Li et al [19] To complete the theory, in this paper an analytical treatment for the comparison of the free energy densities is provided with the same model described in Refs.…”
Section: Introductionmentioning
confidence: 78%
“…[8] Although ferromagnetic states do exist in the neighbourhood of φ e = n + 1/2, the mathematical treatment to provide a flux structure in the vicinity of φ e = n is difficult. The predominant anti-ferromagnetic nearest-neighbour coupling can be described by the bond-order parameter σ, [15,17,21,22] which equals to -1/3 at zero temperature.…”
Section: Discussionmentioning
confidence: 99%